PEMANFAATAN TEPUNG SORGHUM SEBAGAI SUMBER SERAT PANGAN PADA SUBTITUSI RED VELVET TRUFFLE CAKE - Dewi Eka Murniati, Rita Widayanti (Prosiding Pendidikan Teknik Boga Busana, 2020)
Utilization of sorghum flour as food has limitations, one of which is the lack of community knowledge about various types of local cereals that can be consumed. In an effort to introduce local cereals such as sorghum, optimization of patiseri product processing can be done by adding seeds or sorghum flour. In this study the 4D method was used to determine the best formulation of the ratio of wheat flour and sorghum flour in percent (%), namely 60:40, 70:30, 80:20. The results showed the best substitution treatment on red velvet cake truffle sorghum products with a percentage of 80:20, roasting temperature of 180 ° C for 45 minutes. In the chemical properties parameters obtained 120.215% water content, 0.83% ash, 18.55% fat, total protein fk: 6.25 (%) 4.29%, carbohydrate by diff 56.105%, crude fiber 0.995%. And the organoleptic parameters obtained a color value of 3.41, a taste of 3.45, aroma of 3.35, texture of 3.66 and overall of 3.41 which means it was liked. Keywords: Sorghum Subtitution, red velvet cake, gluten-free cake